A NEW APPROACH TO NONLINEAR MIXED DISCRETE PROGRAMMING PROBLEMS - WANG, S.; TEO, K. L.; LEE, H. W. J. (Engineering optimization, 1998)
In this paper a novel method is developed for the numerical solution of a non-linear mixed discrete programming problem. The problem is first transformed into another mixed zero-one discrete optimization problem by replacing each of the discrete variables by a set of new variables with a linear constraint. Each of the new discrete variable sets is then made continuous on [0,1] by introducing a quadratic constraints. Thus the original mixed discrete problem is transformed into a continuous nonlinear optimization problem with constraints. The numerical experiments, performed to demonstrate the effectiveness of the method, show that the method is superior to the previous ones.